1989
DOI: 10.1017/s0025315400032239
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Dietary Sterols and Faecal Contribution of Lipids by the Marine InvertebratesNeomysis Integer, Scrobicularia PlanaandNereis Diversicolor

Abstract: Feeding by marine invertebrates affects dietary lipids as they pass through the gut (Volkmanet al, 1980s; Tanoueet al, 1982; Prahlet al, 1984a, b,1985; Nealet al, 1986; Harvey et ah, 1987,1989). Not only do animals appear to alter the dietary lipids but they also contribute their own lipids to the egested material. Faecal pellets are thus likely to have a lipid composition which has contributions from the ingested food material, the animal itself and the microbial populations residing in the animal's alimentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 44 publications
5
35
1
Order By: Relevance
“…The notable presence of GABA in Arenicola faecal matter (Figs. 2 and 4) suggests that a significant proportion of the microbial activity may occur within the Arenicola gut, and/or on freshly egested material, which is consistent with findings that enteric microbes contribute particular fatty acids to the faeces of several marine invertebrates (Bradshaw et al, 1989), and that gut passage alters the bacterial species composition of ingested material (Plante and Mayer, 1994;Plante, 2010). The fact that faunated microcosms generally showed higher GABA recoveries than the equivalent afaunal controls (Fig.…”
Section: Rapid Losssupporting
confidence: 81%
See 1 more Smart Citation
“…The notable presence of GABA in Arenicola faecal matter (Figs. 2 and 4) suggests that a significant proportion of the microbial activity may occur within the Arenicola gut, and/or on freshly egested material, which is consistent with findings that enteric microbes contribute particular fatty acids to the faeces of several marine invertebrates (Bradshaw et al, 1989), and that gut passage alters the bacterial species composition of ingested material (Plante and Mayer, 1994;Plante, 2010). The fact that faunated microcosms generally showed higher GABA recoveries than the equivalent afaunal controls (Fig.…”
Section: Rapid Losssupporting
confidence: 81%
“…absence from faecal pellets) of compounds including lysine, glutamic acid and glucose. Bradshaw et al (1989Bradshaw et al ( , 1991 have shown that marine invertebrates preferentially assimilate mono-and poly-unsaturated fatty acids over saturated forms, and that certain sterols are not absorbed at all.…”
Section: Introductionmentioning
confidence: 99%
“…It follows earlier studies in which the molecular distributions (e.g. Volkman et al 1980, Prahl et al 1984, Bradshaw et al 1989) and the isotopic compositions (e.g. Des Marais et al 1980, Stott et al 1997, Grice et al 1998, Pancost et al 1999) of individual compounds have been followed through trophic steps.…”
Section: Introductionmentioning
confidence: 63%
“…The microbial culture and light supply were therefore appropriate to promote microphytobenthic growth in the microcosms. At the end of the experiment, mean proportions of PUFA in H. diversicolor were higher than 40%, thus demonstrating that worms were still in a good shape (Bradshaw et al, 1989;Luis and Passos, 1995;Meziane et al, 1997). The FA compositions of worms also differed between starved individuals and those fed with diatoms; particularly, the proportion of 16:1ω7 was significantly higher in worms fed with diatom.…”
Section: Validation Of the Experimental Proceduresmentioning
confidence: 95%